The Influence of Work-Life Balance, Burnout, and Job Satisfaction on the Performance of Maxim Bike Drivers in Bengkulu City - Silalahi , Iren Rosania; Nasution, Nasution (Student Journal of Business and Management, 2024)
This study aims to analyze the effect of work-life balance, burnout and job satisfaction on the performance of Maxim bike drivers in Bengkulu City. The study uses a quantitative descriptive approach using primary data collected through questionnaires. The sample used is the Maxim bike drivers in Bengkulu City, totaling 240 drivers who were taken using the Purposive Sampling method. The data processing of this research used the Statistical Package for Social Science (SPSS) software version 20.0. The analysis used is validity test, reliability test, F test, t test for hypothesis testing and analysis of the coefficient of determination (R²). The results of this study indicate that; 1). Work-life balance has a significant effect on performance of Maxim bike drivers in Bengkulu City. 2). Burnout has a significant effect on performance of Maxim bike drivers in Bengkulu City. 3). Job Satisfaction has a significant effect on performance of Maxim bike drivers in Bengkulu City